Peningkatan Pendapatan Ibu Rumah Tangga Melalui Pelatihan Ketrampilan Payet - Simbolon, Bernadetta Anita Jerry; Heddy, Heddy; Naibaho, Dameria; Saragih, Agus Mariani (Politeknik Negeri Medan, 2023)
PKM is increasing the income of housewives through Sequin Skills Training for Wanita Katovich RI, Tanjung Selamat Branch, Medan Selayang District, Medan City. The training is implemented to make women independent, skillful, have their own income, able to create employment opportunities and improve the family's economy. The specific target of this PKM activity is to enhance the income of housewives by empowering them to Participate in making sequins, enabling women to run their own businesses with limited budgets, and even hire others. This business can be done at home, so women can cope with their tasks as mothers or housewives. The training was held over three days, starting from Friday, 8 September 2023, to Sunday, 10 September 2023, and will be attended by ten participants. The training was guided by an expert instructor named Lidya Oktavia Situmorang. The training was held in the multi-purpose hall of the Santa Maria Ratu Rosary Church on Jalan Flamboyan Raya Medan.